The Impacts of Breakthrough Drug Classes on Total Healthcare Expenditures - Zeynal Karaca; Steven N. Wiggins (Journal of Health Economics and Outcomes Research)
**Background:** Pharmaceutical firms spend billions of dollars developing new therapies, which are often sold at a substantial premium over older therapies. The costs and benefits of these newer and more expensive drugs, however, are controversial. The empirical evidence on whether newer drugs can decrease overall healthcare expenditures may enable private and public health policymakers to develop new drug benefit structures.